DAMPAK MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA DIGITAL QREATIF EDUCATIVE TERHADAP PEMAHAMAN KONSEP IPAS SISWA DI SDN 2 SUKAJADI PURWAKARTA - Ananda Dwi Pratama; Agus Muharam; Gemi Gustiani; Ihsan Rizali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of concept understanding among elementary school students in Natural and Social Sciences (IPAS), particularly on the topic of the states of matter and their changes, which was caused by teacher-centered learning and the limited use of innovative learning media. This study aims to determine the level of students' IPAS concept understanding before and after the implementation of the Problem Based Learning (PBL) model assisted by the Qreatif Educative digital media, as well as to analyze its impact on improving the IPAS concept understanding of fourth-grade students at SDN 2 Sukajadi Purwakarta. This study employed a quantitative approach with a Pre-Experimental One-Group Pretest–Posttest design. The research sample was determined using a saturated sampling technique, involving 32 fourth-grade students. Data were collected through a concept understanding test and analyzed using the N-Gain test and paired samples t-test. The results showed that the average pretest score of 51.56 increased to 72.97 in the posttest, with an average N-Gain of 0.45, categorized as moderate. The paired samples t-test results showed a t-value of 22.48 with a significance of 0.000 (< 0.05), so H0 was rejected and H1 was accepted. It can therefore be concluded that the implementation of the Problem Based Learning (PBL) model assisted by the Qreatif Educative digital media had a positive and significant impact on improving elementary school students' IPAS concept understanding. This study recommends that teachers adopt this model as an alternative approach in IPAS learning, and that future researchers develop research designs with control groups and larger samples. Keywords: Problem Based Learning, Qreatif Educative, concept understanding, IPAS, elementary school